PENGARUH MEDIA APRON HITUNG TERHADAP KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 2 KOTA PEKANBARU - Dede Wahyuni; Wusono Indarto; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations of the numeracy skills of the students have not developed optimally. So we need apron media application count. This study aims to determine the effect of the apron media count towards numeracy skills of children aged 5-6 years in kindergarten Negeri Pembina 2 of Pekanbaru. The sample used in this study 15 people protégé. The data collection techniques were used that observation and documentation. Data were analyzed using t-test using SPSS 20.0. Hypothesis of the study is the use of media activity has an influence on the apron arithmetic numeracy skills of children aged 5-6 years in kindergarten Negeri Pembina 2 of Pekanbaru. It can be seen from the analysis of the data obtained and Sig t = 9,134. (2-tailed) = 0.000. because Sig. (2-tailed) = 0.000 <0.05, it can be concluded that there is a difference in students' numeracy skills significantly after use of media in learning arithmetic apron. So it means Ho rejected and Ha accepted that there shall mean a very significant difference between before and after the experiment by applying apron media count. Apron media influence count towards numeracy skills of children aged 5-6 years in kindergarten Negeri 2 Pekanbaru City Trustees of 48.92%.Keywords: Counting Capabilities, Media Apron Count